Sintesis Partikel Komposit Magnetit/Hidroksiapatit Menggunakan Metode Hidrotermal - Lilis Suriani; Ahmad Fadli; Fajril Akbar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Magnetite/hydroxyapatite composites can be applied in biomedical fields such as drug delivery, orthopedics, protein adsorption/release, hyperthermia therapy, and solid phase extraction from plasmid DNA. The purpose of this study was to study the effect of reaction temperature and hydroxyapatite ratio on the crystallinity, crystal size, particle size, magnetism and morphology of the composites of magnetite/hydroxyapatite synthesized using the hydrothermal method. Composites were synthesized from 2 mmol of FeCl3, 4 mmol of citrate and 6 mmol of urea which were dissolved in 40 ml of distilled water and stirred at 300 ppm using a magnetic stirrer for 15 minutes, then added 7.5 g/L polyethylene glycol and commercial hydroxyapatite of various concentrations (70%, 80% and 90%) and stirred again for 1 hour. Then the suspension was put into a hydrothermal container and in the oven at a temperature of 200oC, 220oC, and 240oC for 12 hours. The magnetite/hydroxyapatite composite particles obtained were then characterized by X-ray Diffraction (XRD), and Vibrating Sample Magnetometer (VSM). The magnetite particles produced are cubicly shaped and hydroxyapatite were hexagonally shaped. The increase in reaction temperature from 200 oC to 240oC at the concentration of magnetite are 10% increased the crystals size of magnetite from 22,87 nm to 24,162 nm and crystal size of hydroxyapatite increased from 26,456 nm to 27,8 nm. While the increase in the concentration of magnetite in composite from 10% and 30% at 240oC increased the crystal size of magnetite from 24,162 nm to 27,472 nm, decreased the crystal size of hydroxyapatite from 27,8 nm to 26,288 nm. Magnetite/hydroxyapatite composite were superparamagnetic with coercivity 0,2 Oe and saturation magnetization (Ms) 4,2 emu/g. Keywords: composite, drug delivery system, hydrothermal, hydroxyapatite, magnetite